2012
DOI: 10.1308/003588412x13171221592375
|View full text |Cite
|
Sign up to set email alerts
|

Buried or unburied K-wires for lateral condyle elbow fractures

Abstract: INTRODUCTIONLateral humeral condyle fractures typically require a longer period of internal fixation than other distal humeral fractures due to the increased risk of non-union. K-wires can be buried and left in situ until union or they can be left unburied and require removal after four weeks, with plaster immobilisation until union. There is no consensus as to whether wire burial is preferable or not. The aim of this study was to determine whether K-wire burial is associated with more complications than non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 12 publications
3
31
1
Order By: Relevance
“…They concluded that leaving the K-wires unburied was safe and more cost effective than using buried wires. However, similar to our previous study [10], the vast majority of the patients were managed with buried wires. Our current study included much more comparable patient numbers, with 60 in the buried and 64 in the unburied group, with a greater potential to show a true difference between the groups.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…They concluded that leaving the K-wires unburied was safe and more cost effective than using buried wires. However, similar to our previous study [10], the vast majority of the patients were managed with buried wires. Our current study included much more comparable patient numbers, with 60 in the buried and 64 in the unburied group, with a greater potential to show a true difference between the groups.…”
Section: Discussionsupporting
confidence: 71%
“…A previous study at our institution [10] noted problems surrounding skin erosion following the routine use of buried wires. This led to a change in practice, such that unburied wires were preferably used.…”
Section: Introductionmentioning
confidence: 88%
“…All the K-wires were unburied in their study. One study looking at buried as well as unburied K-wires in lateral condyle fractures found a higher rate of infection in the buried K-wire group 2. It is difficult to say whether burying or not burying the K-wires has any impact on the development of infection or more specifically the development of TSS, but it should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Displaced fractures often require open reduction and internal fixation. Use of Kirschner wires (K-wires) is the most common method of fracture stabilisation in lateral condyle fracture fixation in children 2. Complications of K-wire usage include failure of fixation, wire breakage, infection and migration 3…”
Section: Introductionmentioning
confidence: 99%
“…But it has been generally accepted that the displaced fractures should be treated with open reduction so as to achieve the near anatomical alignment. [10][11][12][13] Smooth Kirschner wires (K-wire) are the most commonly used metallic implants for fixation of the fracture. 8,14 But this fixation requires an additional immobilization with a plaster splint or a cast for four to six weeks.…”
Section: Comparison Of Kirschner Wires and Cannulated Screw Internal mentioning
confidence: 99%